Diffusion behaviour of corrosive solution environments in carbon black filled modified polyethylene linings - Dinh, Van Chau (ĐHCN, 2016)
The diffusion behaviour of water and HCl solution at different temperatures and concentrations into a modified polyethylene filled with carbon black used for lining is presented. It has shown the predominant role of nature of environment and carbon black content. In the both environments, an increase of environmental temperature increased the capacity of environmental absorption and the diffusion rate. The lower sorption capacity was observed at 40 and 60 o C while a higher at 80o C in the water. The two-stage diffusion appeared for the case of the corrosive environment at 80o C. An increase of carbon black loading was increased both diffusion rate and saturation values. Diffusion of the environment into the polymer proposed by the following: environmental molecules diffusing into the polymer matrix through porous system, were trapped by functional groups on the carbon black surface and polymer molecule chain, and are immobilized. This explains the increase of sorption capacity when increase carbon black loading.